SISTEM ADMINISTRASI PENDAFTARAN PESERTA DIDIK BARU BERBASIS CASH BASIS MENGGUNAKAN WEB DINAMIS - Sindhu Rakasiwi; Yuli Fitrianto; Febryantahanuji Febryantahanuji (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This research was conducted at SMK Widya Praja Ungaran. Every year the Widya Praja Ungaran Vocational School holds a New Student Registration (PPDB) to select prospective students. In the 2018/2019 academic year, 396 people registered and 298 people were accepted. The PPDB process starts from prospective students filling out the registration form and ends with the payment of re-registration funds for accepted students. The system used in the implementation of PPDB is still paper-based so that the performance of the PPDB committee is less effective. The purpose of this study is to design a computer-based new student registration system that is structured in a database to assist the PPDB committee in processing registration participant data, reduce paper purchase costs, minimize the risk of data loss, data corruption, recording and counting errors. Data collection was obtained through observation, interviews, questionnaires and literature study. This system is made using dynamic web with PHP (Hypertext Preprocessor) programming language and MySQL database. The design of this system uses UML (Unified Modeling Language). The development method used is the R&D (Research and Development) method. This study resulted in a cash-based new student registration administration system using a dynamic web to provide convenience for the committee in processing PPDB participant data from the registration process to new student re-registration transactions, as well as presenting reports quickly and accurately. Based on the research conducted, the results obtained from testing the validity of the new system score from internal and external validators. The internal validator with 20 statements obtained a feasibility percentage of 94%. An external validator with 20 statements obtained a feasibility percentage of 97%. From the results of these tests, it can be concluded that the administrative system for registering new students can be a solution to the problems found and can be implemented in the object of research.